Exploring the Prevalence, Risk Factors and Association with Physical Activity of Musculoskeletal Disorders among Patients Attending a Tertiary Teaching Hospital in Gazipur Bangladesh: A Cross-Sectional Study (Central Medical College Journal, 2024)
Background: Musculoskeletal disorders encompass a range of strain-related conditions affecting the musculoskeletal system. Physical activity has been recognized as a protective factor against numerous disabling diseases, including musculoskeletal disorders. This study aims to examine the prevalence of musculoskeletal disorders and investigate its correlation with physical activity in the context of Bangladesh.Methods: This cross-sectional study employed a robust methodology involving the use of standardized questionnaires to assess physical activity levels and musculoskeletal symptoms among 430 patients attending outpatient departments at Gazipur City Medical College. The study period spanned from December 2022 to March 2023, facilitating the collection of valuable data for analyzing the relationship between physical activity and musculoskeletal disorders in this specific population.Results: The study included 430 individuals, with a fairly equal distribution between males (41.9%) and females (58.1%). The majority fell within the 31-40 age range (34.9%). About 42.0% were overweight, while 39.0% had a normal weight. Urban residents constituted 69.8%, and the predominant occupational groups were office workers (23.3%) and garments workers (27.9%). Approximately 60.5% reported co-morbidities, and sedentary behavior was prevalent (70.0% sat for